„Do it yourself“ (DIY) Automated Insulin Delivery (AID) Systems: Stand der Dinge - Heinemann, Lutz; Lange, Karin (Diabetologie und Stoffwechsel, 2019)
Over the past few years, a group of dedicated people with an affinity for technology and type 1 diabetes has developed systems that enable automated insulin delivery (AID). Patients build these AID systems themselves (do it yourself; DIY). The quality of glucose control achieved with DIY AID systems is impressively good, but the effort for users in everyday life is considerable. So far, no results of clinical studies have been obtained that prove these individual experiences.Main obstacles for the use (also by more patients) are legal questions, because DIY AID systems do not represent approved medical devices. They must be regarded as “experimental” systems. As long as patients build and use these systems for themselves and do not endanger other people, they act at their own risk. Legal questions are more complex and more difficult to answer if, for example, a traffic accident occurs. A legal assessment (in particular of the medical situation) of such systems, initiated by the German Diabetes Society (DDG) (see DDG homepage), comes to the following key statements:– From the patient’s point of view, the assembly of a DIY AID system does not constitute a criminal offence. However, since the intended purpose of the devices is violated, there is no liability on the part of the manufacturers of the medical devices used for this purpose.– Patients who assemble DIY AID systems and “sell” them to other patients are liable to prosecution under the Medical Devices Act (MPG).– Doctors do not have to refer patients with type 1 diabetes to DIY AID systems.If a patient expresses interest in such a system or is already using it, the attending physician must inform the patient about the improper use of the medical devices used and about the associated risks. He should document this information accordingly.This overview presents the current status of this development from various points of view.
Keywords: automatisierte Insulindosierung; Insulintherapie; Closed Loop; artifizielles Pankreas